2020
DOI: 10.3390/toxins12030198
|View full text |Cite
|
Sign up to set email alerts
|

Bee Venom Phospholipase A2 Induces Regulatory T Cell Populations by Suppressing Apoptotic Signaling Pathway

Abstract: Bee venom phospholipase A2 is a lipolytic enzyme in bee venom that catalyzes hydrolysis of the sn-2 ester bond of membrane phospholipids to produce free fatty acid and lysophospholipids. Current evidence suggests that bee venom phospholipase A2 (bvPLA2) induces regulatory T cell expansion and attenuates several immune system-related diseases, including Alzheimer’s disease. The induction of Treg cells is directly mediated by binding to mannose receptors on dendritic cells. This interaction induces the PGE2-EP2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 46 publications
(57 reference statements)
0
23
0
Order By: Relevance
“…This ability proposes bPLA2 as an alternative treatment for neuroinflammatory diseases as they mediate antiinflammatory effects [111,115]. A representation of this regulated expression pathway is shown in Figure 4 [111,116]. This Treg expression has been demonstrated to modulate apoptotic signalling and therefore, it possesses immunomodulatory properties [116].…”
Section: Phospholipase A2mentioning
confidence: 99%
See 1 more Smart Citation
“…This ability proposes bPLA2 as an alternative treatment for neuroinflammatory diseases as they mediate antiinflammatory effects [111,115]. A representation of this regulated expression pathway is shown in Figure 4 [111,116]. This Treg expression has been demonstrated to modulate apoptotic signalling and therefore, it possesses immunomodulatory properties [116].…”
Section: Phospholipase A2mentioning
confidence: 99%
“…A representation of this regulated expression pathway is shown in Figure 4 [111,116]. This Treg expression has been demonstrated to modulate apoptotic signalling and therefore, it possesses immunomodulatory properties [116]. Meanwhile, bPLA2 can induce a T helper type-2 (Th2) response that is dependent on MyD88 expression in T cells, inducing an immune protective response against future BV exposure [117].…”
Section: Phospholipase A2mentioning
confidence: 99%
“…PLA2 can bind to cluster of differentiation 206 (CD206), a dendritic cells (DC) surface receptor, and stimulate the secretion of prostaglandin E2 (PGE2). When PGE2 binds to prostaglandin E2 receptor 2 (EP2), forkhead box P3 (Foxp3) will increased expression, causing naïve T helper cells to differentiate into CD4 + CD25 + Foxp3 + Treg cells [ 35 , 36 , 37 ]. Moreover, research showed the portion of resting Treg cell (CD62LhiCD127low) has increased with bvPLA2 treatment [ 36 ].…”
Section: Pharmacological Mechanisms Of the Most Abundant Componentmentioning
confidence: 99%
“…When PGE2 binds to prostaglandin E2 receptor 2 (EP2), forkhead box P3 (Foxp3) will increased expression, causing naïve T helper cells to differentiate into CD4 + CD25 + Foxp3 + Treg cells [ 35 , 36 , 37 ]. Moreover, research showed the portion of resting Treg cell (CD62LhiCD127low) has increased with bvPLA2 treatment [ 36 ]. Ye et al [ 38 ] suggested that bvPLA2 has a neuroprotective effect through microglial deactivation as well as reduction in CD4 + T cell infiltration.…”
Section: Pharmacological Mechanisms Of the Most Abundant Componentmentioning
confidence: 99%
“…A total of 11 studies were published. Three reviews provided a good overview of the therapeutic effect of bee venom [ 6 , 7 , 8 ], and eight original research articles focused on bee venom, melittin, PLA 2 , and apamin [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
mentioning
confidence: 99%